Nível de atividade física no lazer em idosos residentes na região da Vila Clementino no Município de São Paulo - Novais, Francini Vilela [UNIFESP] (2009)
To preserve the autonomy and independence of the elderly has a very relevant with the physical activity during leisure time. Purpose: Believing to be the physical activity to regulate one of the main agents of health promoters and functional independence for the elderly, the aim of this study was to analyze the level of physical activity, particularly in the leisure time of elderly residents in the region of Vila Clementino Municipality of São Paulo (SP). Methods: This is a study of cross with a sample of 135 elderly and 94 females (69.6%). The mean of age was 74.13± 8.5 years, the minimum 60 years, and more than 93 years. For the data of physical activity was used recreation area of the International Physical Activity Questionnaire long version, with the cutoff at 150 minutes per week. We used descriptive analysis, chi-square and multiple logistic regression analysis, the adopted level of significance of p <0.05. Results: 73.3% of the elderly people were considered insufficiently active in leisure. Physical activity during leisure time made so poor was significantly more frequent among women compared with men and among the elderly who are in extreme ranges of education and income, both in crude analysis, and in adjusted analysis. Similarly, the two tests were found positive association between the number of products with the failure of current recommendations for physical activity during leisure time. Conclusions: The results of this study are of importance in identifying a high percentage of elderly insufficiently active in their leisure time, allowing new studies aimed at identifying the reasons and barriers to the practice of regular physical activity and future actions within the public health accrue to this framework.